2016
DOI: 10.1016/j.matbio.2015.11.007
|View full text |Cite
|
Sign up to set email alerts
|

Maturation stage enamel malformations in Amtn and Klk4 null mice

Abstract: Amelotin (AMTN) and kallikrein-4 (KLK4) are secreted proteins specialized for enamel biomineralization. We characterized enamel from wild-type, Amtn−/−, Klk4−/−, Amtn+/−Klk4+/− and Amtn−/−Klk4−/− mice to gain insights into AMTN and KLK4 functions during amelogenesis. All of the null mice were healthy and fertile. The mandibular incisors in Amtn−/−, Klk4−/− and Amtn−/−Klk4−/− mice were chalky-white and chipped. No abnormalities except in enamel were observed, and no significant differences were detected in enam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
27
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 55 publications
2
27
1
Order By: Relevance
“…Our findings on teeth from a patient heterozygous for the AMTN deletion showed a 18.8–24.6% reduction in enamel mineral density compared to control teeth, in contrast, the final mean enamel mineral density achieved across the full enamel thickness in Amtn -/- teeth was reduced by 2.1% and was not significantly different to WT (32,47). Microhardness values for the inner and middle enamel layers in null mice were also no different to WT but the microhardness of the surface layer in null mice was significantly reduced by approximately 23% (47). It was concluded that AMTN plays a crucial role in the production of a normally mineralised enamel surface in rodent mandibular incisors.…”
Section: Discussioncontrasting
confidence: 72%
See 4 more Smart Citations
“…Our findings on teeth from a patient heterozygous for the AMTN deletion showed a 18.8–24.6% reduction in enamel mineral density compared to control teeth, in contrast, the final mean enamel mineral density achieved across the full enamel thickness in Amtn -/- teeth was reduced by 2.1% and was not significantly different to WT (32,47). Microhardness values for the inner and middle enamel layers in null mice were also no different to WT but the microhardness of the surface layer in null mice was significantly reduced by approximately 23% (47). It was concluded that AMTN plays a crucial role in the production of a normally mineralised enamel surface in rodent mandibular incisors.…”
Section: Discussioncontrasting
confidence: 72%
“…In Amtn -/- mice (32,47), the effect on enamel phenotype varied depending on tooth type, with the continually erupting mandibular incisors most affected while molars appeared unaffected and maxillary incisors were merely stained. These differences may be related to the rate of formation/eruption of the different teeth; mandibular incisor enamel has less time in which to fully mineralise prior to eruption and AMTN may be required to ensure that the finished enamel surface is fully mineralised prior to enamel eruption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations